2020
DOI: 10.1177/0961203320972778
|View full text |Cite
|
Sign up to set email alerts
|

A comparative study between the disease characteristics in adult-onset and childhood-onset systemic lupus erythematosus in Egyptian patients attending a large university hospital

Abstract: Introduction Disease features and laboratory abnormalities differ among adult-onset and childhood-onset systemic lupus erythematosus (aSLE and cSLE). Socioeconomic status both independent of, and in combination with, ethnicity influences the disease phenotype and outcome. Objective To compare the various disease features among patients with cSLE and aSLE in a limited monetary income Egyptian cohort attending a large free-of-charge university hospital. Patients and methods: Retrospective analysis of the medical… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 45 publications
0
6
0
Order By: Relevance
“…The geographic differences in age of onset, disease manifestations, and disease activity between different cities in Egypt were noted. In a single-center study on 202 Egyptian JSLE cases, 36 the F:M ratio was lower (2.6:1). A potential explanation could be related to the difference in the number of studied patients; however, the environmental factors cannot be excluded.…”
Section: Discussionmentioning
confidence: 87%
See 1 more Smart Citation
“…The geographic differences in age of onset, disease manifestations, and disease activity between different cities in Egypt were noted. In a single-center study on 202 Egyptian JSLE cases, 36 the F:M ratio was lower (2.6:1). A potential explanation could be related to the difference in the number of studied patients; however, the environmental factors cannot be excluded.…”
Section: Discussionmentioning
confidence: 87%
“…The manifestations and investigations were comparable and differences in disease manifestations compared to cohorts of children from various countries can be attributed to the ethnic and socioeconomic disparities. 19,36,42,43 Data from a national cohort of juvenile SLE patients in the United Kingdom revealed that ethnicity affects both the clinical course and outcome. At diagnosis, Black African/Caribbean patients showed more "classical" laboratory and clinical features when compared to White Caucasian or Asian patients.…”
Section: Discussionmentioning
confidence: 99%
“…Most patients with nephritis were diagnosed between 10 and 19 years of age. Patients with lupus nephritis were followed for a median of 6 years (IQR, [3][4][5][6][7][8][9][10][11], with a median of two (IQR, 1-5) nephrology and four (IQR, 1-7) rheumatology in-person visits per person-year.…”
Section: Evaluation Across Pedsnet Institutionsmentioning
confidence: 99%
“…Data are limited on the comparative effectiveness of most diagnostic and management approaches in childhood SLE. Up to 20% of all SLE cases are diagnosed before age 18 years (1)(2)(3)(4)(5)(6), and 35%-70% develop kidney involvement (2,3,7,8). Lupus nephritis develops earlier and behaves more aggressively in childhood SLE compared with adult-onset SLE (9).…”
Section: Introductionmentioning
confidence: 99%
“…Approximately 15% to 20% of all SLE patients are diagnosed during childhood ( 3 ). Although childhood-onset SLE (cSLE) has similar pathogenesis, clinical manifestations, and immunologic disorders to adult-onset SLE (aSLE), there are some differences between them ( 4 ). There is evidence that cSLE has stronger genetic background and Interferon (IFN) signature ( 5 ).…”
Section: Introductionmentioning
confidence: 99%